2011
DOI: 10.3109/10826084.2011.521460
|View full text |Cite
|
Sign up to set email alerts
|

HIV in the Epicenter of the Epicenter: HIV and Drug Use Among Criminal Justice Populations in New York City, 1980–2007

Abstract: During the 1990s, some of the highest rates of HIV infection in the United States were found among inmates in the New York City jail and prisons systems. This article traces the history of drug use and HIV infection among populations incarcerated in New York City jails and New York State prisons between 1980 and 2007. It describes and analyzes the policies and programs that were initiated to respond to these epidemics and assesses the lessons learned from almost three decades of experience with HIV among popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Researchers have especially focused on tuberculosis (9, 53) and HIV in correctional facilities, although the precise number of people living with HIV behind bars still remains uncertain, in part because estimates based on the U.S. population at large indicate that ~25% of HIV-infected individuals do not know their positive status. New York City jails reflect national trends in a decline of nearly 50% in the percentage of HIV-positive inmates over the course of the 1990s, from 18.4% to 9.7% (30), but despite these gains, HIV prevalence remains ~5 times higher in state/federal corrections than in the general public: 1.6% among male inmates and 2.4% among female inmates, compared with 0.36% in the total U.S. population for 2006 (10, 35, 52, 56, 78). However, blinded seroprevalance studies in New York revealed HIV rates of more than 5% for male and more than 10% for female inmates (56).…”
Section: Health In the Correctional Settingmentioning
confidence: 99%
“…Researchers have especially focused on tuberculosis (9, 53) and HIV in correctional facilities, although the precise number of people living with HIV behind bars still remains uncertain, in part because estimates based on the U.S. population at large indicate that ~25% of HIV-infected individuals do not know their positive status. New York City jails reflect national trends in a decline of nearly 50% in the percentage of HIV-positive inmates over the course of the 1990s, from 18.4% to 9.7% (30), but despite these gains, HIV prevalence remains ~5 times higher in state/federal corrections than in the general public: 1.6% among male inmates and 2.4% among female inmates, compared with 0.36% in the total U.S. population for 2006 (10, 35, 52, 56, 78). However, blinded seroprevalance studies in New York revealed HIV rates of more than 5% for male and more than 10% for female inmates (56).…”
Section: Health In the Correctional Settingmentioning
confidence: 99%
“…Other oppressed individuals may turn to alcohol and/or other drugs to numb the pain of discrimination, oppression, poverty, and hopelessness. Substance use increases engagement in health risk behaviors such as prostitution, sharing needles, and unprotected sex thereby exacerbating HIV/HCV risk (Arasteh & Jarlais, 2009; Freudenberg, 2011). …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Second, injecting drug use – a highly efficient mode of transmission – along with tattooing and sexual activity (both consensual and otherwise), are commonplace in carceral settings, and as research conducted in the UK and elsewhere has shown, sharing needles and syringes is far from unusual (Turnbull et al , 1993; Yirrel et al , 1997; Case et al , 1998). These factors – high HIV rates on entry to prison, combined with high-risk activity once inside – combine to create an environment that fosters HIV risk and transmission (Freudenberg, 2011; Chen et al , 2008). In many countries prisoners have inadequate access to either prevention information or equipment (such as clean syringes, substitution therapies or condoms; see, e.g., Elliott, 2007) that can reduce or eliminate risk, and this has led to a number of well-documented outbreaks, both of HIV and other blood-borne and sexually transmitted infections (Caplinskiene et al , 2003; Reid et al , 2012).…”
Section: Elements Of the Hiv Legiscapementioning
confidence: 99%